PENGEMBANGAN INSTRUMEN AWAL TWO-TIER MULTIPLE CHOICE UNTUK MENGATASI MISKONSEPSI SISWA PADA MATERI PENGUKURAN BERAT DAN PANJANG KELAS III SEKOLAH DASAR - Sari Efriyani; Yantoro; Andi Gusmaulia Eka Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a two-tier multiple-choice diagnostic instrument to address student misconceptions regarding weight and length measurement in third-grade elementary school. This research was motivated by the limited use of initial assessments capable of uncovering students' thought processes, resulting in the ineffectiveness of misconception detection at the beginning of the lesson. The method used was Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at SD Negeri 155/I Sungai Buluh, with 16 third-grade students as subjects. Data collection techniques included observation, interviews, validation sheets, and tests. The validation results showed a 90% percentage, categorized as highly valid. The reliability test obtained a Cronbach's Alpha value of 0.839, categorized as reliable. Item analysis showed all items were valid with good levels of difficulty and discriminatory power. The effectiveness test showed the instrument was able to identify 31% of misconceptions, categorized as moderate. Therefore, the developed instrument is deemed suitable for use as an initial assessment in elementary school mathematics learning.